The projection of climate change impact on the fatigue damage of offshore floating photovoltaic structures - Zou, Tao; Niu, Xinbo; Ji, Xingda; Chen, Xiuhan; Tao, Longbin (Frontiers in Marine Science, 2023)
In marine environment, floating photovoltaic (FPV) plants are subjected to wind, wave and current loadings. Waves are the primary source of fatigue damage for FPVs. The climate change may accumulatively affect the wave conditions, which may result in the overestimation or underestimation of fatigue damage. This paper aims to present a projection method to evaluate the climate change impact on fatigue damage of offshore FPVs in the future. Firstly, climate scenarios are selected to project the global radiative forcing level over decadal or century time scales. Secondly, global climate models are coupled to wind driven wave models to project the long-term sea states in the future. At last, fatigue assessment is conducted to evaluate the impact of climate change on fatigue damage of FPVs. A case study is demonstrated in the North Sea. A global-local method of fatigue calculation is utilized to calculate the annual fatigue damage on the FPVs’ joints. The conclusions indicate that there are decreasing trends of significant wave height and annual fatigue damage in the North Sea with the high emission of greenhouse gases. The fatigue design of FPVs based on the current wave scatter diagrams may be conservative in the future. The manufacture cost of FPVs can be reduced to some extent, which is beneficial to the FPV manufacturers.